THE RELATIONSHIP OF RAINFALL TO FOOD PRODUCTIVITY ON THE ISLAND OF JAVA - Saputro, Wahyu Adhi; Harahap, Fitri Amalinda; Firdauzi, Indrawan; Dewati, Rosita (Universitas Veteran Bangun Nusantara, 2025)
The high productivity of food crops that occurs in Java Island certainly cannot be separated from the existing rainfall. The availability of water that meets the needs of rice and corn plants will certainly allow plants to grow and develop optimally. The purpose of this study was to determine the relationship between rainfall and food crop productivity in Java Island. This study is a descriptive analytical study using secondary data sourced from the Central Statistics Agency from 2015-2014. The selection of the Java Island research location is because this region contributes more than 50% of the national rice and corn production supply. The data analysis method used is the Pearson correlation. Based on the results of the study, it can be seen that the highest average rice productivity is owned by West Java Province with a rice productivity achievement of 58.64 quintals per hectare, while the highest corn productivity achievement occurred in the same location with an average of 76.58 quintals per hectare. Based on the results of the study, it was also found that there is a relationship between rainfall and rice and corn productivity in Java Island. This is indicated by the significance value of both being less than the alpha value of 5%. In addition, the relationship between rainfall and rice productivity is in the moderate category, while the relationship between rainfall and corn productivity is in the low category. Keywords: Rainfall, Corn, Rice, Productivity